Z nanooblaganjem do izboljšanja biokompatibilnosti vsadkov - Dolenc, Andrej (Medicinski razgledi, 2006)
Biocompatibility of different materials in the body is very complicated phenomenon. Although structural characteristics of implant are decisive for its specific purpose, biologic response mainly depends on surface characteristics of the implant and its interaction with biologic environment. Nanolayering of the implant to improve biocompatibility presents a recent innovation in this field of research. One method of nanolayering is layer-by-layer assembly which has many advantages over other nanolayering methods. The method is based on alternate adsorption of oppositely charged components on a hard surface, allowing for exact control of composition and thickness of the coating in a nanometer range. It was shown that with a properselection of polymer components the biocompatibility of used and tested structural material with good mechanical characteristics can be improved. The following article presents a view on biocompatibility of implants and highlights some cases of nano-modified surfaces and their potential applications.
Keywords: Biokompatibilni materiali; Implants, Artificial; Materiali, testiranje; Materials Testing; Biocompatible Materials; Mikrokemija; medical device; medicinski pripomočki; Microchemistry; vsadki; materiali; biomateriali; biokompatibilnost; nanomateriali